HISTORY OF THE DEVELOPMENT OF LEGAL TECHNIQUE (World Bulletin of Management and Law, 2022)
The article highlights the history and development trend of theoretical of application of legal techniques in different periods – the old, the middle ages, a new period and the latest period. Special attention is paid to the work of scientists who have made a significant contribution to the development of legal techniques in the years of independence and improvement of lawmaking.